Ressonâncias do discurso do presidente Michel Temer proferido em 2017 em homenagem ao dia da mulher : misoginia e feminismo em contradições - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
Founded by the assumptions of the Analysis of the French line, this work aims to analyze the discursive mobilization promoted by the then President of the Republic Michel Temer when giving a speech in honor of the women's day on March 8, 2017 and also analyzing comments from internet users published on a Youtube’s website on which the video was released, considering the discourse resonances. The aim is to identify the misogynistic framework present in the president's pronouncement and to demonstrate how the inscription to feminism occurs from such an event. In addition, it’s intend to demonstrate the discursive inconsistencies represented in the event, Foucault's theory of representation of discursive eruptions constructed through the produced relation of meaning. To this end, the research is part of the methodology of analysis of the field of French AD, based mainly on notions about machismo, according to Pierre Bourdieur (1989) (2018), in discourse and history for Michel Foucault (1987). (1988) (1996) (1997) (2000) (2002) and Judith Butler's (2017) assumptions for understanding the feminist movement and its interfaces. It is required through the analysis based on French AD to contribute about discursive studies that unravel the dominance of the male gender in the female society and demonstrate the ideologically constituted and socio-historically established misogynist and machista inferences. As results of this research we can affirm that the question proposed in this research brought to light interpretative notions based on the postulates in the French Line Speech Analysis demonstrating how the production conditions of the statements may emerge in society as a whole, therefore, we consider that a talk precedes a do and this is how the inferiorizing stereotypes in relation to women and their placements in the social market retrofeed in search of the maintenance of the masculine hegemony.
Resonances of president Michel Temer’s speech delivered in 2017 in honor of women’s day: misogyny and feminism in contradictions
Keywords: Análise do discurso; Michel Temer; Dia da mulher; Discourse analysis; Woman's day; LINGUISTICA, LETRAS E ARTES